Identification of Ore Mineral and Host Rocks in Balukang Area, Sojol District, Donggala Regency, Central Sulawesi Province - Kacong, Nurhijah Awaludin; Asrafil, Asrafil; Puspita, Riska (Universitas Negeri Gorontalo, 2026)
The Balukang area, Sojol District (Donggala Regency, Central Sulawesi), is characterized by dioritic intrusions and active artisanal mine workings that expose mineralized rocks. This study aims to identify the presence of ore minerals, determine their host rocks, and understand the relationship between geological conditions and ore mineral formation in the area. Sampling was carried out at several observation stations identified in the field. Limited exposure restricted the sampling process, so some samples were taken from man-made mining pits that were still accessible. From all the samples collected, four representative samples were selected for petrographic analysis and six representative samples for mineralographic analysis. Petrographic thin sections and polished sections were examined using transmitted- and reflected-light microscopy to characterize mineral assemblages and textures. The analysis results showed the presence of ore minerals such as silver, gold, pyrite, chalcopyrite, sphalerite, covellite, galena, and hematite, with observed textures including intergrowth, replacement, open space filling, and mutual boundary. These textural relationships indicate hydrothermal deposition and provide a basis for interpreting mineral paragenesis in the study area. The ore minerals are associated with quartz diorite and quartz porphyry diorite as host rocks, which are controlled by intrusion lithology and geological structures. Overall, the identified mineral assemblage and host-rock association offer an initial mineralogical baseline to guide exploration targeting along veins, fractures, and stockwork zones. This study is a preliminary study, so further research is needed through detailed geological mapping, geochemical analysis, and fluid inclusion studies.